Isolated diastolic hypertension in childhood and risk of adult subclinical target organ damage: a 30-year prospective cohort study. Issue 8 (21st August 2022) - Liao, Yueyuan; Chu, Chao; Wang, Yang; Zheng, Wenling; Ma, Qiong; Hu, Jiawen; Yan, Yu; Yang, Jun; Yang, Ruihai; Wang, Keke; Yuan, Yue; Chen, Chen; et al.
Abstract : Background: Data on the association of isolated diastolic hypertension (IDH) in childhood with adult cardiovascular risk are scarce. This study aimed to estimate the prevalence of IDH in adolescents and to explore the impact of IDH in childhood on adult subclinical target organ damage (STOD). Methods: This longitudinal study consisted of 1738 school children (55.4% boys) aged 6–15 years from rural areas of Hanzhong, Shaanxi, who were followed for 30 years. Their blood pressure was recorded to define the hypertension subtypes: normotension, IDH, isolated systolic hypertension (ISH) and mixed hypertension. Tracked STOD included arterial stiffness ( n  = 1738), albuminuria ( n  = 1652) and left ventricular hypertrophy (LVH) ( n  = 1429). Results: Overall, the prevalence of IDH, ISH and mixed hypertension was 5.4, 2.2 and 3%, respectively, and there was no gender difference. Over 30 years, 366 (21.1%) of participants developed arterial stiffness, 170 (10.3%) developed albuminuria and 68 (4.8%) developed LVH. Compared with normotensive participants, IDH in childhood had higher risk ratio (RR) of experiencing arterial stiffness (RR, 1.66; 95% CI, 1.01–2.76) and albuminuria (RR, 2.27; 95% CI, 1.35–4.16) in adults after being fully adjusted but not LVH. However, if the elevated blood pressure in children was used as the reference standard, IDH in childhood was associated with adult LVH (RR, 2.48; 95% CI, 1.28–4.84). Conclusion: IDH accounts for a higher proportion of adolescent hypertension subtypes and can increase the risk of adult STOD. These results highlight the necessity of improving the prevention, detection and treatment of IDH in adolescents.